KAJIAN ETIKA TELEOLOGIS DALAM NOVEL 9 MATAHARI KARYA ADENITA - , DESTI ANDIKAWATI, Dra. Hj. Jirzanah, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Research entitled The Teleological Ethics Study of Novel 9 Matahari by Adenita is an attempt to understand the values and morals messages. The story of the novel about a student who worked hard to reach her dreams, to study at college. Every problems had came and donât make her spirit down, such as family conflicts and finance. The story can give motivation for the young generation to never give up in study, with any problems come. The research try to reveals the ethical values inside the novel in order to gives comprehension to the readers, especially for the young generation, so they can cope problems that blocked during the education process. Teleological ethics used as formal object to analyze the ethical values that contained in the novel from the side of purpose. The purpose of the research are to understand the ethical, to find the moral messages, and to discover the relevance to the people, especially the young generation. The Research is qualitative research in philosophy. The type of research is historical factual of book and used a library research. The study began with data collection, classification of primary and secondary data, systematization data, and analysis of results. Methodical elements are used as a tool to analyzing data are description, interpretation, holistic, and hermeneutics . The results of the study are, first, the ethical values contained in the novel 9 Matahari is sincerity, firmness, persisence, generosity, and religious or spiritual values. The fifth values have been analysed by teleological ethics can be categorized into a stream of ethical egoism. Second, the moral messages from the content of this novel are, each counts for fellow human beings, never give up on things, and learn to forgive the mistakes of others. Third, the relevance of the novel 9 Matahari to the young generation as a motivaton and gives moral comprehension to continue reaching the purpose and dreams, so they will be a strong and morally personal.